Labour Market Developments in the Maritime Industry of the South Baltic Region - Bernacki, Dariusz (Comparative Economic Research. Central and Eastern Europe, 2014)
There are two aims of this study. The first is to outline the developments in the maritime economy and employment in the South Baltic Region, and the second to identify the emerging activities in the maritime industry and to reveal the prospects and potential for labour market development, taking into account the demand for labour, required professions, qualifications of the labour force, and feasible cross-border mobility. This comparative study refers to four EU Baltic coast regions, namely the Mecklenburg-Vorpommern (D), Zachodniopomorskie (PL), Pomorskie (PL) and Klaipeda (LT) regions. Prospects for the economic development and employment potential specified for each region and selected segments of the maritime economy are consequently elaborated. The analysis of the maritime economy in the South Baltic Region reveals some crucial differences in terms of strategic maritime activities and employment potential and prospects for each of the regions. The phenomenon of the diverse demand for labour force through the various segments of the maritime economy and by region has been identified and is presented in the form of a comprehensive matrix of the projected demand for labour.